Localization of receptor site on insect sodium channel for depressant β-toxin BmK IT2. - Huiqiong He (PLoS ONE, 2011)
BACKGROUND: BmK IT2 is regarded as a receptor site-4 modulator of sodium channels with depressant insect toxicity. It also displays anti-nociceptive and anti-convulsant activities in rat models. In this study, the potency and efficacy of BmK IT2 were for the first time assessed and compared among four sodium channel isoforms expressed in Xenopus oocytes. Combined with molecular approach, the receptor site of BmK IT2 was further localized. PRINCIPAL FINDINGS: 2 µM BmK IT2 strongly shifted the activation of DmNa(v)1, the sodium channel from Drosophila, to more hyperpolarized potentials; whereas it hardly affected the gating properties of rNa(v)1.2, rNa(v)1.3 and mNa(v)1.6, three mammalian central neuronal sodium channel subtypes. (1) Mutations of Glu(896), Leu(899), Gly(904) in extracellular loop Domain II S3-S4 of DmNa(v)1 abolished the functional action of BmK IT2. (2) BmK IT2-preference for DmNa(v)1 could be conferred by Domain III. Analysis of subsequent DmNa(v)1 mutants highlighted the residues in Domain III pore loop, esp. Ile(1529) was critical for recognition and binding of BmK IT2. CONCLUSIONS/SIGNIFICANCE: In this study, BmK IT2 displayed total insect-selectivity. Two binding regions, comprising domains II and III of DmNa(v)1, play separated but indispensable roles in the interaction with BmK IT2. The insensitivity of Na(v)1.2, Na(v)1.3 and Na(v)1.6 to BmK IT2 suggests other isoforms or mechanism might be involved in the suppressive activity of BmK IT2 in rat pathological models.